Individuals With Higher CD4/CD8 Ratio Exhibit Increased Risk of Acute Respiratory Distress Syndrome and In-Hospital Mortality During Acute SARS-CoV-2 Infection - Pascual-Dapena, Ana; Chillaron, Juan José; Llauradó, Gemma; Arnau-Barres, Isabel; Flores, Juana; Lopez-Montesinos, Inmaculada; Sorlí, Luisa; Luis Martínez-Pérez, Juan; Gómez-Zorrilla, Silvia; Du, Juan; García-Giralt, Natalia; Güerri-Fernández, Robert (Frontiers in Medicine, 2022)
BACKGROUND: CD4:CD8 ratio has been used as a quantitative prognostic risk factor in patients with viral infections. This study aims to assess the association between in-hospital mortality and at admission CD4:CD8 ratio among individuals with acute SARS-CoV-2 infection. METHODS: This is a longitudinal cohort study with data of all consecutive patients admitted to the COVID-19 unit at Hospital del Mar, Barcelona, Spain for ≥48 hours between March to May 2020.. The CD4+ CD8+ T-cell subset differentiation was assessed by flow cytometry at admission as well as a complete blood test. Patients were classified according to CD4:CD8 ratio tertiles. The primary outcome was in-hospital mortality and the secondary outcome was acute respiratory distress (ARDS). RESULTS: A total of 338 patients were included in the cohort. A high CD4:CD8 ratio (third tertile) was associated with a higher in-hospital mortality (adjusted Cox model HR 4.68 [95%CI 1.56-14.04, p=0.006], reference: second tertile HR 1). Similarly, a high CD4:CD8 ratio (third tertile) was associated with a higher incidence of ARDS (adjusted logistic regression model OR 1.97 [95%CI 1.11-3.55, p=0.022] reference: second tertile HR 1). There was a trend of higher in-hospital mortality and incidence of ARDS in patients within the first tertile of CD4:CD8 ratio compared with the second one, but the difference was not significant. No associations were found with total lymphocyte count or inflammatory parameters, including D-dimer. CONCLUSION: CD4:CD8 ratio is a prognostic factor for the severity of COVID-19, reflecting the negative impact on prognosis of those individuals whose immune response has abnormal CD8+T-cell expansion during the early response to the infection.